PTH-002 Out of hour colonoscopy; is the quality as good as in hour colonoscopy?. Issue 2 (June 2019) - Afify, Shimaa; Archer, Thomas; Thoufeeq, Mo
Abstract : Introduction: Colonoscopy is the 'gold standard' investigation for assessment of the large bowel which detects and prevents colorectal cancer, as well as non-neoplastic conditions. The quality of UK colonoscopy has improved as in 2013 The Joint Advisory Group (JAG) on GI Endoscopy suggests monitoring key performance indicators such as cecal intubation rate (CIR) and the adenoma detection rate (ADR). There has been a drive to improve utilization of endoscopy units nationwide by offering out of hours (OOH) endoscopy to deal with increasing service demands. Our aim was to investigate the quality of colonoscopies carried out during evening and Saturday lists in our unit and compare against BSG standards of quality for colonoscopies. The endoscopy team consisted of our team. Method: We retrospectively collected and analyzed demographical and procedure related data for non- screening colonoscopies performed between January 2016 and April 2018. Procedures were grouped according to the day of the week and timing of session (weekday, evening and Saturday). We also compared those performed by advanced colonoscopist and non-advanced colonoscopist. Advanced colonoscopist was defined as a BCSP colonoscopist or an advanced EMR colonscopists. Results: There were a total of 13642 colonoscopies that were carried out. 26.3% (n=3601) involved patients were >70 years and 73.7% (n=10041) were <70 years. Table 1 summarizes the differences between weekdays, evening and Saturdays' colonoscopies regarding the CIR and ADR. We noted that the KPIs (ADR, CIR) met the JAG standards. Advanced colonoscopists had better KPIs when compared to the non-advanced colonoscopists. Conclusion: JAG standards were maintained during colonoscopies done on weekdays, evening and Saturdays. Advanced colonoscopists had higher CIR and ADRs.